Advances in Micro-Bioreactor Design for Organ Cell Studies - Carl-Fredrik Mandenius (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Micro-bioreactors offer unique opportunities to study biological systems under fluidic conditions. The concept of micro-bioreactors suggests that biological reaction conditions on a large scale can be scaled down to micro-volumes while maintaining performance and functionality. Models and operation principles can be simulated at a smaller scale, either by scaling down organs in the human body, or using bioreactors for the production of biologics. This book highlights these issues with a strong focus on new engineering design. The initial chapters cover the conceptual design of microbioreactors and organ-on-chips, and the role of microbioreactors in tissue engineering for clinical and therapeutic targets. Two chapters are dedicated to microbioreactors for implementing tumor models. Other chapters discuss three-dimensional models for hepatic and cardiac cells for toxicity testing and drug evaluation. Finally, the design of organ chips for cartilage scaffolds and the integration of sensors are covered in separate chapters. We believe the book will have substantial value for researchers active in bioreactor engineering, drug development and cell physiology, as well as readers interested in these topics.